Aktivitas Pembiayaan Multi Jasa Barokah (MJB) di BMT UGT Nusantara Capem Jember Kota - Al Karimatus Sa'idah; Adinda Iklilatul Aura Salsabila; Fitri Musyarrofatin Nailiyah (CV. ITTC INDONESIA, 2024)
This research discusses the financing activity of Multi Jasa Barokah (MJB) at BMT UGT Nusantara Capem Jember Kota, which is one of the sharia financing products that uses the ijarah contract. This researchoaims to understand the mechanism of MJB financing, analyze the factors that influence the demand and supply of MJB financing, evaluate the performance and risk of MJB financing, and provide recommendationsoto improve the effectivenessoand efficiency of MJB financing. This research uses a qualitative methodowith data collection techniques through observation, interviews, and documentation. The results of the study showothat MJB financing has several advantages, such as transactions in accordance with sharia, fast and easy process, competitive ujrah, flexible tenure and installment system, and no fines or penalties for late payment. However, MJB financing also faces some challenges, such as the availability of funds, management policies, operational performance, economic, social, and competitive conditions, as well as credit, liquidity, and operational risks. Therefore, the author gives some suggestions, such as increasing fund raising, quality of feasibility analysis, service and promotion, as well as internal control and compliance.